(untitled) (Revista Brasileira de Pesquisa em Saúde/Brazilian Journal of Health Research, 2024)
Introduction: Behçet’s disease is a chronic, multisystemic, inflammatory syndrome characterized by recurrent attacks of oral and genital ulcers, in addition to cutaneous, ophthalmic, central nervous system, gastrointestinal and vascular involvement. Other manifestations may occur more rarely, such as pulmonary artery aneurysm and pulmonary artery thrombosis. Case report: We report a case of a woman presenting with dyspnea and hemoptysis secondary to pulmonary artery aneurysms and pulmonary artery thrombosis caused by Behçet’s disease as the first clinical manifestations. Conclusion: Anticoagulation in thrombosis, without the use of immunosuppressants in patients with Behçet’s Disease, may lead to a poor outcome, as the underlying vasculitis will not be treated. The clinical suspicion of this condition has prognostic implications, especially in atypical presentations, emphasizing the relevance of the theme exemplified in this case report.